Laboratory monitoring of COVID-19 patients and importance of coagulopathy markers - J. H. Khizroeva (Акушерство, гинекология и репродукция, 2020)
The pandemic of a novel coronavirus infection COVID-19 has become a real challenge to the mankind and medical community and has raised a number of medical and social issues. Based on the currently available information on COVID-19 clinical cases, it follows that COVID-19 patients in critical condition exhibit a clinical picture of disseminated intravascular coagulation (DIC), septic shock with developing multiple organ failure, which justifies use of anticoagulant therapy in COVID-19 patients. In addition to isolating virus RNA from biological material and polymerase chain reaction diagnostics, use of simple and easily accessible laboratory blood markers is necessary for management of COVID-19 patients. If the activation of coagulation processes is sufficient enough, consumption of platelets and blood clotting factors can be diagnosed by laboratory methods as prolongation of routine blood clotting tests and increasing thrombocytopenia. Hyperfibrinogenemia, increased D-dimer level, prolonged prothrombin time, thrombocytopenia, lymphopenia, leukocytopenia, increased concentration of interleukin-6 and ferritin are observed in most COVID19 patients. The degree of increase in these changes correlates with severity of the inflammatory process and serves as a prognostically unfavorable sign. Here we discuss value of laboratory monitoring playing an essential role in such pathological crisis that contributes to patient screening, diagnosis as well as further monitoring, treatment and rehabilitation.